Study of (GIS) and Remote Sensing Applications in Forest Resource Management - Amn, Shahidullah; Safi , Mohibullah; Sadat, Said Rahmatullah (Journal of Natural Sciences – Kabul University, 2026)
The purpose of this study was to identify the uses of Geographic Information Systems (GIS) and remote sensing in forest resource management and to identify their opportunities and limitations. This technology has brought significant changes in the management, conservation, and monitoring of forests. Methodologically, the study is descriptive and analytical, utilizing both literature sources and satellite data. The results show that (GIS) and remote sensing have wide applications in determining vegetation cover, estimating biomass and carbon stocks, monitoring climate change, mapping, wildfire management, assessing biodiversity, and creating tourist areas and other fields. However, these technologies have the potential to provide free information, but the lack of reliable data, high costs, seasonal effects, and other similar problems are among their limitations. The presence of analytical capabilities and technical tools is considered essential for their effective use in forests.